2005
DOI: 10.1021/jp044510h
|View full text |Cite
|
Sign up to set email alerts
|

Excitation, Ionization, and Fragmentation of Chiral Molecules in Asymmetric Microenvironments:  A Mass-Resolved R2PI Spectroscopic Study

Abstract: One- and two-color, mass selected R2PI spectra of the S(1) <-- S(0) transitions in the bare (R)-(+)-1-phenyl-1-propanol and its complexes with bidentate solvent molecules, like the (R)-(-)- and (S)-(+)-3-hydroxytetrahydrofuran enantiomers, have been recorded after a supersonic molecular beam expansion. The one-color R2PI excitation spectra of the diastereomeric complexes are characterized by three main peaks, one red-shifted and the other two blue-shifted relative to the band origin of the most stable anti con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 25 publications
4
13
0
2
Order By: Relevance
“…The formation of the adducts with the three P R rotamers has been excluded by comparisons with the excitation spectra of the complexes of P R with analogues monodentate solvents (ciclopentanol, tetrahydrofuran, and secondary alcohols. 120 Therefore, the a2g bands of Figure 16 have been attributed to the three dominant isomeric forms I, II, and III reported in Figure 15a.…”
Section: Furanose Rings Analogues: R-and S-3-hydroxytetrahydrofuranmentioning
confidence: 92%
See 3 more Smart Citations
“…The formation of the adducts with the three P R rotamers has been excluded by comparisons with the excitation spectra of the complexes of P R with analogues monodentate solvents (ciclopentanol, tetrahydrofuran, and secondary alcohols. 120 Therefore, the a2g bands of Figure 16 have been attributed to the three dominant isomeric forms I, II, and III reported in Figure 15a.…”
Section: Furanose Rings Analogues: R-and S-3-hydroxytetrahydrofuranmentioning
confidence: 92%
“…More recently, we focused our attention on the study of chiral molecules of biological or pharmaceutical interest, or tailor-made complexes containing components which mimic the building blocks of large biomolecules. More specifically, we investigated the effects of inter-and intramolecular interactions in the structure and spectral properties of complexes containing chiral fluoroaromatics, 118 furanose rings analogues, 119,120 esters, 121 and neurotransmitters. 80 The Effect of Fluorine Substitution on Chiral Recognition R-1-Phenylethanol (E R ) and R-1-Phenyl-2,2,2-trifluoroethanol (FE R ) of R-and S-2-Aminobutane…”
Section: Supramolecular Diastereomersmentioning
confidence: 99%
See 2 more Smart Citations
“…The quantification was done by measuring the relative peak intensity of the complexes in mass spectrometer [40 -47]. Speranza applied ESI-MS n CID and REMPI-TOF methodologies to measure the fragmentation thresholds of diastereomeric clusters [19,23,25,32,48,49]. They found that the chiral recognition was very sensitive to cavity size and hydrophilic/hydrophobic properties of the chiral receptor [24,50].…”
mentioning
confidence: 99%